New dispersive [Formula Presented] force and s-shell hypernuclei - Shoeb, Mohammad; Neelofer, Nasra; Usmani, Q.N.; Rahman Khan, M.Z. (American Physical Society, 1999)
Variational Monte Carlo calculations for the ground- and excited-state binding energies of s-shell hypernuclei using a new form of dispersive spin-dependent noncentral [Formula Presented] force have been made to study its effect on the overbinding problem of [Formula Presented] and on the spin dependence of [Formula Presented] force. A detailed analysis shows that the strength of the dispersive [Formula Presented] force can be adjusted to resolve the overbinding problem using two-body correlations alone. Consequently, the ambiguity in the strength of the dispersive [Formula Presented] force masks the effect of 2π-exchange [Formula Presented] force and [Formula Presented] correlations on the data. The contribution of the dispersive force to the [Formula Presented] spin-flip splitting of [Formula Presented] hypernuclei is not uniquely determined. Further [Formula Presented] data favor a small spin dependence of the [Formula Presented] potential, a situation characteristically similar to other versions of dispersive [Formula Presented] potentials. © 1999 The American Physical Society.